TRANSFORMATIONAL LEADERSHIP AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR ON PERFORMANCE: A STUDY ON NURSES AT THE REGIONAL GENERAL HOSPITAL OF KENDARI CITY - Nuraena, Siti; Tosepu, Ramadhan; Saptaputra, Syawal Kamiluddin (Preventif Journal, 2024)
ABSTRACT The success of an organization fundamentally depends on the skills and abilities of those who establish it. The resources possessed by an organization, such as methods and technology, will not function optimally if they are not supported by human resources with optimum performance. This research investigates the influence of transformational leadership and organizational citizenship behavior on the performance of nurses at the Regional General Hospital of Kendari City. The study employs a quantitative approach involving 45 respondents. The data analysis technique used is SEM PLS. The research findings reveal a strong correlation between Transformational Leadership and Organizational Citizenship Behavior with the performance of nurses at the Regional General Hospital of Kendari City. Leadership that is capable of inspiring and motivating staff, coupled with a high level of Organizational Citizenship Behavior, significantly impacts the improvement of nurse performance. These results underscore the importance of a leadership culture that motivates and allows for voluntary engagement in the healthcare work environment. The implications of this research can provide valuable guidance for hospital management in enhancing the quality of nursing services and, ultimately, healthcare services for the community in Kendari City. These findings also offer valuable guidance for hospital management to develop strategies and maximize the full potential of every member of the nursing team, thereby enhancing performance. As a result, patients will benefit from better and higher-quality care. Keywords: Transformational Leadership, OCB, Performance